Mapping mycological ignorance – checklists and diversity patterns of fungi known for West Africa - Meike Piepenbring; Jose G. Maciá-Vicente; Jean Evans I. Codjia; Carola Glatthorn; Paul Kirk; Yalemwork Meswaet; David Minter; Boris Armel Olou; Kai Reschke; Marco Schmidt; Nourou Soulemane Yorou (IMA Fungus)
Abstract Scientific information about biodiversity distribution is indispensable for nature conservation and sustainable management of natural resources. For several groups of animals and plants, such data are available, but for fungi, especially in tropical regions like West Africa, they are mostly missing. Here, information for West African countries about species diversity of fungi and fungus-like organisms (other organisms traditionally studied by mycologists) is compiled from literature and analysed in its historical context for the first time. More than 16,000 records of fungi representing 4843 species and infraspecific taxa were found in 860 publications relating to West Africa. Records from the Global Biodiversity Information Facility (GBIF) database (2395 species), and that of the former International Mycological Institute fungal reference collection (IMI) (2526 species) were also considered. The compilation based on literature is more comprehensive than the GBIF and IMI data, although they include 914 and 679 species names, respectively, which are not present in the checklist based on literature. According to data available in literature, knowledge on fungal richness ranges from 19 species (Guinea Bissau) to 1595 (Sierra Leone). In estimating existing species diversity, richness estimators and the Hawksworth 6:1 fungus to plant species ratio were used. Based on the Hawksworth ratio, known fungal diversity in West Africa represents 11.4% of the expected diversity. For six West African countries, however, known fungal species diversity is less than 2%. Incomplete knowledge of fungal diversity is also evident by species accumulation curves not reaching saturation, by 45.3% of the fungal species in the checklist being cited only once for West Africa, and by 66.5% of the fungal species in the checklist reported only for a single country. The documentation of different systematic groups of fungi is very heterogeneous because historically investigations have been sporadic. Recent opportunistic sampling activities in Benin showed that it is not difficult to find specimens representing new country records. Investigation of fungi in West Africa started just over two centuries ago and it is still in an early pioneer phase. To promote proper exploration, the present checklist is provided as a tool to facilitate fungal identification in this region and to aid conceptualisation and justification of future research projects. Documentation of fungal diversity is urgently needed because natural habitats are being lost on a large scale through altered land use and climate change.